Abccheck technique in teaching narrative writing for ESL primary school students - Marzaizah Binti Che Awang (2022)
Primary students’ performance in the aspect of English narrative writing needs to be given particular attention as this element is one of the essential parts of the new curriculum for primary school introduced by the Ministry of Education since the year 2016. A few past studies have investigated the effectiveness of the process writing approach to students’ writing quality. However, studies on specific techniques on the process writing approach to suit the approach for the primary school students are scarce. Therefore, the present study focuses on investigating the effectiveness of the technique called the ABCCHECK Technique. Pre- and post- tests of narrative writing tasks were conducted for 60 selected primary school students in two schools. Later, further analysis was conducted to explore the students’ perception of the usage of the technique in assisting them in their narrative writing. This research utilized a quasi- experimental approach, and data collection involved qualitative and quantitative. The subjects in this study were primary school students in two different schools in Kuala Krai, Kelantan. The results showed a significant difference between the performance of students from both the experimental and control groups after the pre-post-tests. However, the experimental group score is much higher than the control group score. Furthermore, all respondents in the interview demonstrated positive perceptions of the usage of the technique in assisting their guided narrative writing. The students in general reported that ABCCHECK Technique is an effective technique for them to learn narrative writing as it is easy, understandable, fun, and helpful. To conclude, ABCCHECK Technique using process writing approach could guide students in narrative writing and also promote positive teaching and learning strategies.